A Microdosing Study with 99mTc-PHC-102 for the SPECT/CT Imaging of Primary and Metastatic Lesions in Renal Cell Carcinoma Patients - Oana C. Kulterer; Sarah Pfaff; Wolfgang Wadsak; Nathalie Garstka; Mesut Remzi; Chrysoula Vraka; Lukas Nics; Markus Mitterhauser; Franziska Bootz; Samuele Cazzamalli; Nikolaus Krall; Dario Neri; et al. (2020)
99mTc-PHC-102 is a 99mTc-labeled derivative of acetazolamide, a high-affinity small organic ligand of carbonic anhydrase IX (CAIX). 99mTc-PHC-102 has previously shown favorable in vivo biodistribution properties in mouse models of CAIX-positive clear cell renal cell carcinoma (ccRCC) and colorectal cancer. In this study, we aimed to explore the targeting performance of 99mTc-PHC-102 in SPECT in patients with renal cell carcinoma while also assessing the safety and tolerability of the radiotracer. Methods: We studied 5 patients with localized or metastatic ccRCC in a microdosing regimen, after the administration of a 50-μg total of CAIX ligand and 600-800 MBq of 99mTc-PHC-102. Tissue distribution and residence time in normal organs and tumors were analyzed by serial SPECT/CT scans at 3 time points (30 min, 2 h, and 6 h) after intravenous administration. Results: In the 5 patients studied, 99mTc-PHC-102 was well tolerated and no study drug-related adverse events were recorded. In the stomach, kidneys, and gallbladder, the radiotracer showed a rapid initial uptake, which cleared over time. Localization of the study drug in primary tumors of 5 patients was observed, with favorable tumor-to-background ratios. 99mTc-PHC-102 SPECT/CT allowed the identification of 4 previously unknown lung and lymph node metastases in 2 patients. Conclusion:99mTc-PHC-102 is a promising SPECT tracer for the imaging of patients with ccRCC. This tracer has the potential to identify primary and metastatic lesions in different anatomic locations. 99mTc-PHC-102 might also serve as a companion diagnostic agent for future CAIX-targeting therapeutics.